The use of contextual information in expert tennis anticipation - Murphy, C.; Jackson, R. C.; Williams, A. M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The ability to read and effectively adapt to upcoming events is commonly regarded as an important component of expert performance. The expert advantage in anticipation has been regularly demonstrated in sport and other domains, with particular focus on how experts extract and process information from the visual display more effectively than their less expert counterparts. However, research investigating how contextual information contributes to anticipation is scarce. Dittrich`s (1999) interactive encoding model proposes that in dynamic, multi-element situations, performers extract motion information and temporal relationships between features, mapping this information onto past or potential experiences. In this way the information presented becomes meaningful with respect to complex memory representations. The aim of the study was to assess expert tennis players` ability to anticipate ball bounce location relative to depth and direction in the absence of superficial kinematic information using a simulated laboratory-based anticipation task. Methods: 16 expert and 20 recreational participants viewed footage of rallies from professional tennis matches in normal video (NV) and animation (ANI) display conditions. The ANI condition, which was created using player movement and ball trajectory data, showed the same points as the NV condition but without superficial player kinematics. The players and the ball were represented by two cylinders and a yellow dot respectively, while rackets were not visible. Participants viewed 90 experimental trials in both conditions, between 3 and 13 shots long, on a 4.05X2.29m projection screen from a distance of 5m. Participants anticipated ball bounce location when the final shot was occluded at the opponent`s racket-ball contact. Response accuracy (RA) was recorded as the percentage of correct responses in relation to depth, direction and both depth and direction together. Results: There were significant display and group effects for depth, direction and both (p<.01). Experts` mean RA scores were significantly better than recreational players for depth (NV: 84.58±3.14% vs 80.28±4.79%; p<.01, ANI: 69.31±4.42% vs 65.83±5.41%; p<.05) and both depth and direction together (NV: 62.01±4.45% vs 52.94±5.99%; p<.001, ANI: 49.10±4.00% vs 44.00±6.61%; p<.01). Discussion: The findings imply that experts can still anticipate significantly better than recreational players in the absence of superficial player kinematic information. This is consistent with Dittrich`s (1999) model, as expert tennis players appear to utilise dynamic relational information from the visual display in the form of players` court positioning to anticipate more effectively than recreational players.